BEST: A software to verify the feasibility of urban bus line electrification. (May 2022) - Valentini, M.P.; Conti, V.; Orchi, S.
Abstract: Taking advantage of Public Transport "Open Data" in GTFS (General Transit Feed Specification) format, ENEA developed BEST, a DSS(Decision Support System) able to identify which lines are more suitable, both technically and economically, for the use of BEBs (Battery Electric Buses). The work was carried out within the Italian Research Program on the Electric System (2015–2018 period) and in the last months of the research it was upgraded, acquiring the results of a measurement campaign on the on-field energy consumption of trolleybuses equipped with batteries for a certain flexibility and autonomy. For a given urban line, BEST Better Electric Solution for public Transport): verifies the possibility of adopting BEBs for any recharge solution (only at depot, or both at depot and terminals, or possibly also at intermediate stops), considering the energy needed for the whole peak-day long or for the worst run; individuates which of the feasible recharge solutions is preferable in economic terms; compares costs and benefits, both internal and external, of the electric alternatives respect to diesel and Compressed Natural Gas (CNG). For the case study of Rome's Public Transport (PT) network, the solution with the opportunity charge at terminals usually outperforms the other two in terms of technical feasibility and economic convenience. Choosing Electric buses results more convenient than conventional alternative in about 30% cases.